2013
DOI: 10.4187/respcare.02471
|View full text |Cite
|
Sign up to set email alerts
|

Correlations Between Gait Speed, 6-Minute Walk Distance, Physical Activity, and Self-Efficacy in Patients With Severe Chronic Lung Disease

Abstract: BACKGROUND Four-meter gait speed (4MGS) has been associated with functional capacity and overall mortality in elderly patients, and may easily be translated to daily practice. We evaluated the association of 4MGS with meaningful outcomes. METHODS In 70 subjects we conducted the 4MGS, 6-min walk test (6MWT), objectively measured physical activity, and assessed dyspnea, quality of life, and self-efficacy for walking and routine physical activity. 4MGS was measured in 3 separate time epochs during the 6MWT, to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 41 publications
5
45
0
2
Order By: Relevance
“…Our results also showed a statistically significant difference between groups regarding physical performance as assessed by SPPB (p \ 0.001) and 4MGS (p = 0.002). We performed the 4MGS evaluation in agreement with DePew et al that consider gait speed as a potential ''vital sign'' to be recorded in any medical assessment and an objective measure of the whole organism functioning [27]. The association between vitamin D and appendicular muscle functioning might be explained by the linkage between 1,25(OH) 2 D 3 , active form of vitamin D, and VDR [28], leading to increased protein synthesis and muscle cell growth [15].…”
Section: Discussionmentioning
confidence: 99%
“…Our results also showed a statistically significant difference between groups regarding physical performance as assessed by SPPB (p \ 0.001) and 4MGS (p = 0.002). We performed the 4MGS evaluation in agreement with DePew et al that consider gait speed as a potential ''vital sign'' to be recorded in any medical assessment and an objective measure of the whole organism functioning [27]. The association between vitamin D and appendicular muscle functioning might be explained by the linkage between 1,25(OH) 2 D 3 , active form of vitamin D, and VDR [28], leading to increased protein synthesis and muscle cell growth [15].…”
Section: Discussionmentioning
confidence: 99%
“…Th e sample size calculation was based on the literature, with the expected correlation ( r ) between 6MWT and gait speed assumed to be 0.7 14 and the correlation between physical activity level and gait speed assumed to be 0.3. 29 We selected the lowest correlation in the sample size calculation. Determined with a probability of type I error ( a ) of 0.05, power (1 2 b ) of 0.9, and correlation of 0.3, the calculated sample size was 113, and considering a possible 15% dropout rate, the fi nal sample size was 130.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown a link between gait speed and exercise capacity for patients with COPD. 12,13 However, those studies did not evaluate the several commonly described gait speed protocols and have not established the effect of distance walked, pace, or timing methods on the reliability and reproducibility of gait speed results in patients with COPD. Prior studies using fast pace 14,15 have not investigated the commonly used distances (4 and 10 meters) or the possible timing systems.…”
Section: Introductionmentioning
confidence: 99%